Pemanfaatan Aplikasi Android Belajar Membaca Untuk Meningkatkan Keterampilan Membaca Siswa - Zhalzabilah, Zhalzabilah; Hisbullah, Hisbullah; Firman, Firman (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to determine the description of students' learning activities using the Android learning-to-read application and to determine the improvement in students' reading skills in class I at SDN 41 Batu Putih, Palopo City. The type of research used is Classroom Action Research (PTK) consisting of several stages, namely planning, implementation, observation or observation, and reflection. The focus of the research is to improve students' reading skills by using the learning-to-read Android application. The research subjects were all class I students at SDN 41 Batu Putih, Palopo City, totaling 26 students. The data collection techniques used were observation, interviews, tests, and documentation, then analyzed qualitatively and quantitatively. The results of this research show that in cycle I the description of student learning activities in meeting I got a percentage of 27% (poor), meeting II was 36% (poor), and meeting III was 55% (good). The average overall score percentage in cycle I was 39% (less). In cycle II, the description of student learning activities in meeting I got a percentage of 61% (good), meeting II was 86% (very good), and meeting III was 100% (very good). The average overall score percentage in cycle II was 82% (very good). The percentage of students' reading ability in cycle I got a percentage of 39% (poor) and in cycle II got percentage of 82% (very good). Based on the results of the percentage of learning activities and improvement in students' reading skills using the learning to read an android application, it can be concluded that students experienced an increase in their reading skills through using the "Belajar Membaca" android application.